Glycaemic efficacy of an expanded dose range of dulaglutide according to baseline glycated haemoglobin (HbA1c) subgroup: Post hoc analysis of AWARD‐11. Issue 12 (14th September 2021) - Frias, Juan P.; Bonora, Enzo; Cox, David A.; Bethel, M. Angelyn; Kwan, Anita Y.M.; Raha, Sohini; Malik, Raleigh E.
Abstract: The AWARD‐11 trial demonstrated the safety and efficacy of dulaglutide 3.0 and 4.5 mg compared to dulaglutide 1.5 mg in patients with type 2 diabetes inadequately controlled with metformin. This post hoc analysis examined the change from baseline in glycated haemoglobin (HbA1c) and proportions of patients achieving HbA1c <7% at weeks 36 and 52 with dulaglutide 1.5 mg, 3.0 mg or 4.5 mg across clinically relevant baseline HbA1c subgroups (<8%; 8.0% to < 9.0%; 9.0% to < 10%; and ≥ 10%). Mean reductions in HbA1c were observed across all baseline HbA1c subgroups at 36 weeks (range of HbA1c change: 1.5 mg: −1.0% to −2.2%; 3.0 mg: −1.2% to −2.5%; and 4.5 mg: −1.2% to −3.2%). More patients randomized to 3.0 mg or 4.5 mg (vs. 1.5 mg) achieved HbA1c <7% at 36 weeks regardless of baseline HbA1c; the difference in proportions was greater at higher baseline HbA1c ( P ‐interaction = 0.096). Similar patterns in glycaemic improvement and proportions achieving HbA1c <7% were observed at 52 weeks. Hypoglycaemia and gastrointestinal adverse events were similar among the HbA1c subgroups. Glycaemic control was improved with dulaglutide dose escalation from 1.5 mg to 3.0 mg or 4.5 mg across baseline HbA1c subgroups (<8%; 8.0% to < 9.0%; 9.0% to < 10%; and ≥ 10%).